Studi Pengelolaan Paket Wisata One Day Tour Di Kabupaten Semarang - Aditama Fauzy Rozaqi; Fitriyah .; Lusia astrika (Journal of Politic and Government Studies, 2016)
STUDY OF ONE DAY TOUR MANAGEMENT AS A TOURISMPACKAGES IN SEMARANG DISTRICT.ABSTRACTAutonomy regions is a government affairs transferred to manage their ownhousehold. One of the choices of the government affairs is tourism. Tourism is a new lifestyleindustry which is can fulfill to providing the faster economical growth in the labor sector,income, the standard of living. There’s a thousand regions in Indonesia which is has aincredible tourism potential, nevertheless that potential is never be uncultivated with themaximum of seriousness. This tourism potential could bring in more tourists who couldbecome local revenue. Therefore this case of One Day Tour as a tourism packages broughtby Department of Youth, Sports and Tourism in Semarang district evidently afford brilliantand creative idea which has contributed to develop tourism industry. This packages hasreached their heyday in 2009 at the most of the tourists number, however after establishedsince 2006 this packages had to face into the worst condition in 2012, by decreasing thenumber of the visitors and became a unsustainable program. Therefore the formulation of theproblems are :” Why the One Day Tour as the tourism packages brought by Department ofYouth, Sports and Tourism in Semarang district which is established since 2006 are notsustainability? While this regions has the incredible natural and tourism potential?Based on the issues discussed, this research used qualitative research methods withanalytical descriptive research type. The aim of this research was to understand how theprocess of the One Day Tour management and also explains how the program run and whatinhibiting factors faced by the managers.It can be concluded that at the beginning One Day Tour is managed by a person fromDepartment of Youth, Sports and Tourism in Semarang District. The founder of the One DayTour proved that these packages could reach a lot of visitors in 3 years period from 2006until 2009 with more than 17.640 Tourists. After reached with good record, and achieves atthe heyday these packages experienced a period of low tide in 2010 till 2012 with a decreaseof 52%. Even nowadays in 2016 this packages getting into the worst condition and can beconclude that this program is totally failed and not sustainable. This case happened due thispackages doesn’t have any supported from the government; there is no public privatepartnership and low power of human resources.Recommendation that the writers can conclude is Government should increasing thehuman resources and take seriously this package into an official program.Keywords: Potential, Tourism, Program, Sustainability, Regional Autonomy, GovernmentChoices Affairs, Industry.